Pathogenetic value of cell infiltrate in immunoinflammatory rheumatic diseases - M. Z. Saidov (Медицинская иммунология, 2021)
Cell infiltrate is a morphological substrate of immunoinflammatory rheumatic diseases. The systemic wide progressive disorganization of loose fibrous connective tissue is accompanied by the loss of tolerance with its own autoantigenes, activation of macrophagal-monocyte cells and autoreactive clones of T and B lymphocytes. Hyperproduction of pro-inflammatory chemokines and cytokines, local adhesive ligandreceptor interactions, endothelial reaction and angiogenesis contribute to the formation of cell infiltrate, ectopic lymphoid structures and GZT-granulomas in situ. The autoimmune response is the result of successive systemic and local molecular cellular events in which the mechanisms of congenital and adaptive immunity are involved. When interpreting immunopathogenesis of rheumatic diseases, all models and schemes adopted in the field of fundamental immunology are used. This is a model of MHC-restrictions, a model of molecular mimicry, or cross of the antigen presentation, a model of disrupting central or peripheral tolerance to auto-antigens, a model of candidate “triggers” of autoimmune and autoinflammatory processes, a model of associations of alleles MHC I and II classes with specific, nosologically unique, rheumatic diseases.